Stable Isotope Oscillations in Whale Baleen Are Linked to Climate Cycles, Which May Reflect Changes in Feeding for Humpback and Southern Right Whales in the Southern Hemisphere - Dedden, Adelaide V.; Rogers, Tracey L. (Frontiers in Marine Science, 2022)
Baleen whales that undertake extensive long-distance migrations away from reliable food sources must depend on body reserves acquired prior to migration. Prey abundance fluctuates, which has been linked in some regions with climate cycles. However, where historically these cycles have been predictable, due to climate change they are occurring at higher frequencies and intensities. We tested if there were links between variability in whale feeding patterns and changes in climate cycles including the El Niño-Southern Oscillation (ENSO), Southern Annular Mode (SAM), and Indian Ocean Dipole (IOD). To reconstruct feeding patterns we used the values of bulk stable isotopes of nitrogen (δ15N) and carbon (δ13C) assimilated within the baleen plates of 18 humpback and 4 southern right whales between 1963 and 2019, then matched them with climate anomalies from the time in which the section of baleen grew. We show that variability in stable isotope values within baleen for both humpback and southern right whales is linked with shifts in climate cycles and may imply changes in feeding patterns due to resource availability. However, these relationships differed depending on the oceanic region in which the whales feed. In the western Pacific, Southern Ocean feeding humpback whales had elevated nitrogen and carbon stable isotope values during La Niña and positive SAM phases when lagged 4 years, potentially reflecting reduced feeding opportunities. On the other hand, in the Indian Ocean the opposite occurs, where lower nitrogen and carbon stable isotope values were found during positive SAM phases at 2–4-year lag periods for both Southern Ocean feeding humpback and southern right whales, which may indicate improved feeding opportunities. Identifying links between stable isotope values and changes in climate cycles may contribute to our understanding of how complex oscillation patterns in baleen are formed. As projections of future climate scenarios emphasise there will be greater variability in climate cycles and thus the primary food source of baleen whales, we can then use these links to investigate how long-term feeding patterns may change in the future.